Kajian volume dan nilai impor komoditas dan implikasinya pada pengembangan infrastruktur - Welendo, La; Nuhun, Ridwan Syah; Abdillah, Muh Fiqram; Apriansyah, Aris; Putra, Pandu Wartaning (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study analyses the volume and value of commodity imports in Southeast Sulawesi in 2024 and its impact on infrastructure development in the region. Rapid economic growth in Southeast Sulawesi has increased the demand for imports of various commodities, including mineral fuels, metals, and chemical products. Ports as the main entry point for imports are under capacity pressure, while limited road infrastructure slows down the distribution of goods to various regions. This study uses a descriptive quantitative method with secondary data that includes the volume and value of imports per commodity type. The results show that increasing import volumes, especially for fuels and metals, require strengthening port infrastructure and transport networks to support efficient distribution. In addition, dependence on fossil fuels emphasises the importance of renewable energy development to improve energy security. Recommendations include strengthening port infrastructure, developing transport networks transport network, as well as investment in alternative energy. It is hoped that this research can serve as a reference for local governments in planning sustainable infrastructure development to support economic growth in Southeast Sulawesi.